2006
DOI: 10.2353/ajpath.2006.051054
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β and Signaling of Interleukin-1 in Vascular Wall and Circulating Cells Modulates the Extent of Neointima Formation in Mice

Abstract: Interleukin (IL)-1 is an important mediator of inflam- to IL-1R1؉/؉ (P < 0.05) but had significantly greater neointima/media than IL-1R1 ؊/؊ to IL-1R1 ؊/؊ controls (P < 0.05). These data confirm the importance of IL-1␤ signaling in mediating arterial neointima formation and suggest the involvement of IL-1 signaling in both circulating and arterial wall cells. Furthermore, receptor antagonism may be a better therapeutic target than interruption of IL-1␤ processing or release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 36 publications
3
72
0
Order By: Relevance
“…In order to identify the hematopoietic cells within the neointima, we analyzed carotid artery cross sections utilizing specific cell surface antigens for the presence of lymphocytes, mast cells, and macrophages. Lymphocytes, mast cells, and macrophages are all inflammatory cells that secrete growth factors and cytokines that have been implicated in neointima formation (25)(26)(27). Further, our group has demonstrated that neurofibromin is a critical regulator of Ras activation in both lymphocytes and mast cells in vitro and in vivo (14,28).…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify the hematopoietic cells within the neointima, we analyzed carotid artery cross sections utilizing specific cell surface antigens for the presence of lymphocytes, mast cells, and macrophages. Lymphocytes, mast cells, and macrophages are all inflammatory cells that secrete growth factors and cytokines that have been implicated in neointima formation (25)(26)(27). Further, our group has demonstrated that neurofibromin is a critical regulator of Ras activation in both lymphocytes and mast cells in vitro and in vivo (14,28).…”
Section: Resultsmentioning
confidence: 99%
“…2) provides a new physiologic indicator for the inflammatory response evidenced by neointimal formation. IL-1β is not only a marker but rather a mediator of SMC proliferation [18], that is important in neointimal formation [19]. However, the correlation was not precise since there was no marked reduction in IL-1β arterial levels in the preconditioned group to correlate with the significant reduction in neointimal formation observed in this group.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Moreover, IL-1ra-deficient mice are more prone to neointima development after endothelial injury and more prone to atherogenesis. 7,8 Administration of IL-1 to porcine coronary arteries leads to neointimal formation, whereas balloon angioplasty results in increased levels of IL-1␤ at the injured segment of the porcine coronary artery but not at uninvolved sites.…”
Section: Cardiac-related Effects Of Il-1 and Il-1ramentioning
confidence: 99%